사물인터넷 기술을 활용한 여름철 도로 가로공간의 실시간 온도지도 서비스 구현 - 오재규(Jae-Kue Oh); 김광석(Gwang-Seok Kim); 김지윤(Ji-Yoon Kim); 최윤수(Yun-Soo Choi) (디지털콘텐츠학회논문지, 2022)
도로 가로공간은 가장 기본적인 도시 교통 인프라이며, 가장 개방적인 도시 공간이다. 과거에는 도로 가로공간이 교통 인프라로만 인식하여 도로 공간의 온도와 환경자원으로써의 가치는 부차적으로 파악하였다. 따라서, 도로 구간 기온을 관리해야 할 필요성이 있으며 이를 효율적으로 관리하기 위하여 도로 열 현상을 실시간으로 도면화할 필요가 있다. 본 연구에서는 도로 공간의 기온을 실시간으로 반영할 수 있는 시스템을 개발하고 도면화한다. 서울의 강서구 도로 일부 구간을 실험지역으로 삼아 온도를 계측할 수 있는 사물인터넷 도구를 개발하였다. 그리고 이 계측 결과를 도로 공간정보에 반영할 수 있는 시스템을 구축한다. 이 실험 결과를 근거로 도로 공간의 온도정보 반영을 통하여 시범 시스템의 효용성 여부를 검증하고 향후 발전방안을 도출하였다. Roadside space is the most basic urban transportation infrastructure and the most open urban space. in the past, roadside space was recognized only as a transportation infrastructure, so the temperature of roadside space and its value as an environmental resource were secondary to that. Therefore, it is necessary to control the temperature of road sections and to draw road heat phenomena in real time to efficiently manage them. In this study, the system is developed and visualized by reflecting the temperature of roadside space in real time. An internet of Things tool has been developed to measure temperature using part of Gangseo-gu road in Seoul as an experimental area It also establishes a system that can reflect the results of this measurement in road spatial data. Based on results of this experiment, the pilot system was verified by reflecting the temperature information of the roadside space and a future development plan was derived. KCI Citation Count: 0